Analisis Kadar Surfaktan Anionik Pada Air Sungai Barito Menggunakan Metode Spektrofotometri Visible - Nurul Fajriah; Tuti Alawiyah; Ikna Urwatul Wusko (Jurnal Pelayanan Kefarmasian dan Sains, 2020)
ABSTRACT BACKGROUND: Water is one of the resources that contains the main needs including humans, animals and plants. Indonesia is a country that has a lot of air resources and is known as a maritime country consisting of thousands of islands. Indonesia also has more than 500 rivers. One of them is the Barito River located in Ulu Benteng Village RT.11 Barito Kuala Regency is still used by the community for daily needs. One of them is used for clothing and drinking water sources. OBJECTIVE: To determine and compare the levels of anionic surfactants in the Barito river with different time intervals, namely the 1st, 4th and 7th days. METHODS: This research uses descriptive research with group design. The population and sample used were all of the Barito River water with inclusion and exclusion criteria using the Visible Spectrophotometer method. RESULTS: Significant value of the results of calculations using SPSS of 0.593 with the results of the value of the relationship coefficient (r) 0.997 and the results of the first day level of 4 mg/L, day 4 of 2 mg/L and day 7 of 2, 8 mg/L which determines levels exceeding the normal threshold that has been determined by Government Regulation No. 82 of 2001 which is 0.2 mg/L. CONCLUSION: Anionic surfactant content in the Barito River water has a value that exceeds the threshold of Government Regulation Number 82 Year 2001, namely on day 1 of 4 mg/L, day 4 of 2 mg/L and day 7 of 2,8 mg/L. The significance value is 0.593 which means that there is no time difference and the hypothesis is rejected. Keywords: Visible Spectrophotometer, Barito River, Anionic Surfactant